NSDHL Depletion Promotes Cellular Senescence in Mouse Embryonic Fibroblasts - L.R. Gabitova; I.A. Astsaturov (Учёные записки Казанского университета: Серия Естественные науки)
Cholesterol, its derivatives, and metabolites from its biosynthesis are important components of the cell and play an essential role in many intracellular processes, including cell signaling, regulation of the cell cycle, etc. In this paper, it has been shown that depletion of the cholesterol biosynthesis pathway enzyme NSDHL (NAD(P)H-dependent steroid dehydrogenase-like) and accumulation of its metabolites lead to an increased rate of cellular senescence and reduction of proliferation in mouse embryonic fibroblasts. The phenomenon described can be useful for developing new strategies of targeting cholesterol biosynthesis pathway in cancer cells in order to increase their senescence and inhibit proliferation.